Role of lipotoxicity in insulin resistance in subtotally nephrectomized mouse model - Laetitia Koppe; Caroline Pelletier; Roxane Vella; Denis Fouque; Fitsum Guebre-Egziahber; Christophe Soulage (The Korean Society of Nephrology, 2012)
Chronic kidney disease (CKD) is associated with a large range of metabolic alterations among which insulin resistance and dyslipidemia. We hypothesize that a phenomenon of lipotoxicity and ectopic fat redistribution could be responsible for the insulin-resistance associated to CKD. C57BL/6 mice underwent a 5/6 nephrectomy and were compared to pair fed sham-operated mice. Insulin sensitivity was estimated through intra-peritoneal insulin (ipITT) and glucose tolerance (ipGTT) tests. Anthropometric (body weight, lean and fad pad mass) and metabolic parameters (glycemia, insulin, cholesterol, triglycerides) were measured. The phosphorylation of a key protein of insulin signaling pathway (protein kinase B, PKB/Akt) was studied by Western blot. The intra-muscular and intra-hepatic lipids were extracted using Chloroform-Methanol (2:1, v/v). The CKD mice exhibited a marked decrease in insulin sensitivity (−76%, p<0.01) and altered glucose tolerance (+24%, p<0.001). CKD mice exhibited a profile of insulin resistance. CKD mice exhibited a significant decrease in white adipose tissue accretion (−57%, p< 0.001) associated with increased muscle (+138%, p<0.05) and liver (+38%, P<0.05) lipid contents compared to sham-operated mice. The CKD mice presented a blunted insulin-induced Akt phosphorylation (−34%, p<0.05) in gastrocnemius muscle. In subtotally nephrectomized mouse model we showed an ectopic intramuscular and intrahepatic lipid redistribution concomitant with insulin resistance. Insulin resistance and lipotoxicity may represent the missing links (beyond the classical cardiovascular risk factors) that may help explain the increased risk of cardiovascular disease in CKD.